Study on the Hepatoprotection of Schisandra chinensis Caulis Polysaccharides in Nonalcoholic Fatty Liver Disease in Rats Based on Metabolomics - Feng, Yanbo; Li, Han; Chen, Cong; Lin, Hao; Xu, Guangyu; Li, He; Wang, Chunmei; Chen, Jianguang; Sun, Jinghui (Frontiers in Pharmacology, 2021)
The aim of this study was to investigate the hepatoprotection of Schisandra chinensis Caulis polysaccharides (SCP) in the nonalcoholic fatty liver disease (NAFLD) induced by high-fat diet (HFD) in rats. Thirty Wistar rats were randomly divided into control group (CON), model group (MOD) and Schisandra chinensis caulis polysaccharide (SCP) group. Except for those in CON group, the other rats were fed with high-fat diet for 4 weeks to establish a NAFLD model. From the 5th week, rats in SCP group were given SCP solution (100 mg·kg-1) by gavage for 6 weeks, and those in CON and MOD groups were given an equal volume of distilled water in the same way. The serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) levels were detected. The small molecular metabolites in the blood of rats were determined by the metabolomics method of ultra-high performance liquid chromatography-quadrupole/electrostatic field orbitrap high-resolution mass spectrometry (UHPLC-Q-Orbitrap-MS/MS) combined with multivariate analysis. The enrichment analysis and pathway analysis of the different metabolites were carried out. The therapeutic mechanism of SCP in NAFLD rats was verified by Western blot. The results showed that the levels of AST, ALT, TG, TC and LDL-C in the serum of rats in SCP group were significantly lower, and the levels of HDL-C were significantly higher than those in MOD group. The screening and analysis of the metabolic pathways showed that SCP could alleviate the development of NAFLD by regulating the expression of UDP-glucose pyrophosphorylase (UGP2), UDP-glucose 6-dehydrogenase (UGDH), acetyl CoA carboxylase (ACC) and fatty acid synthase (FAS) in the blood of NAFLD rats. This study may provide a theoretical basis for the development and utilization of SCP.